Strategies of the privatization - ابوبكر عبدالعزبز; محمد ليلى (Dirasat in Economics and Business, 2006)
Referring to the domination of the public sector and the government intervention in the economical aspects through the 1960s and 1970s of the previous century in most of the countries especially the developing and arab countries this dominathon was represented in constructing the infrastructure and public projects which was playing adecisive role in the economical and social development nevertheless government intervention in the economical aspects resulted in many outcomes represented in government withdrawal from its essential tasks and its principal role to organize the society and legislation to achieve justice security and freedom for all citizens besides an increase of the public expenditure which lead to the aggravation of the public failure deceleration of the economical development averages and deficit of the public economical units. This Study derived its importance from the rarity of the empirical studies which can point out the privatization subject in libya , besides many sub-targets.